2022
DOI: 10.1021/acs.analchem.2c01486
|View full text |Cite
|
Sign up to set email alerts
|

Vapor Generation of Rare-Earth Elements via Reaction with Tetrahydroborate: Chemical Identities and Mechanisms of Formation

Abstract: This technical note reports for the first time the simultaneous vapor generation of 16 rare-earth elements (REEs) via reaction with sodium tetrahydroborate (THB). Significant improvement in REE vapor generation efficiency was discovered in the presence of arsenazo III (ARS). Subsequent to a critical evaluation on the impacts of various experimental variables, including the concentrations of acids, THB, and ARS, blank-limited (reagent contamination and impurity from ARS) detection limits (LODs) in the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Huang et al 188 investigated the determination of Ti isotopes using fs-LA-MC-ICP-MS. Following signal stability optimisation, external reproducibility of d 49 Ti/ 47 Ti was estimated as ±0.07& for spot-to-spot analysis. However, it was found that mineral matrix effects had a signicant effect on accuracy and robust data could only be achieved using matrix-matched RMs as the bracketing standard.…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al 188 investigated the determination of Ti isotopes using fs-LA-MC-ICP-MS. Following signal stability optimisation, external reproducibility of d 49 Ti/ 47 Ti was estimated as ±0.07& for spot-to-spot analysis. However, it was found that mineral matrix effects had a signicant effect on accuracy and robust data could only be achieved using matrix-matched RMs as the bracketing standard.…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 99%
“…Results were evaluated using SRM3162a alongside the SRM979 Cr standard using its certied 53 Cr/ 52 Cr of 0.11339. A range of igneous RMs were measured for d 49 Ti/ 47 Ti with an estimated reproducibility of ±0.047& (2 sd).…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several high efficiency sampling systems have been proposed for REEs determination by ICP-MS, including membrane desolvation (MD), 18 electrothermal vaporization (ETV), 19 and plasma-induced chemical vapor generation (PICVG). [20][21][22] However, MD is limited by its high cost and signicant memory effect, and ETV is poorly repeatable and typically requires the use of modiers to overcome severe matrix interference. PICVG is green and highly effective, but it needs to use a collision/reaction cell (CRC) to reduce the oxide ratio caused by the introduction of a large amount of moisture, which sacrices the sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In analytical chemistry, generation of volatile species has been widely used to enhance sample introduction, especially for atomic spectrometry such as inductively coupled plasma mass spectrometry (ICPMS), optical emission spectrometry (ICP-OES), atomic absorption spectrometry (AAS), and atomic fluorescence spectrometry (AFS), yielding high transport efficiency and efficient matrix separation through different derivatization strategies of chemical, , electrochemical, sonochemical, etc. , Compared with other strategies, photochemical vapor generation (PVG) , assisted by ultraviolet (UV) radiation owns lots of comparative advantages, including less reagent consumption and waste production, minimized interference from transition metals, improved stability of plasma (low hydrogen generation), etc. …”
Section: Introductionmentioning
confidence: 99%